Verb "giving" in Japanese: Review of natural semantic metalanguage - Sukma, Luh Putu Ratnayanti (Journal of Language and Pragmatics Studies, 2024)
The intricacies of Japanese verbs related to the concept of "giving" present a compelling area of study, reflecting the nuanced nature of language and cultural expression. Despite the significance of these verbs in everyday communication, there has been limited research that systematically maps their semantic distinctions. This study addresses this gap by exploring the meaning configuration of key Japanese verbs associated with the concept of giving. Building on previous linguistic analyses, this research employs the Natural Semantic Metalanguage (NSM) theory to provide a more detailed explication of the verbs ageru, kureru, suru, and tsukeru. The data, sourced from "Minna no Nihongo" Volumes I and II as well as internet sources, were collected through an observation method combined with note-taking. The analysis reveals subtle yet significant differences in how these verbs are used, particularly in relation to the types of entities involved and the context of their application. The findings contribute to a deeper understanding of Japanese verb semantics, offering valuable insights for both linguistic theory and practical language learning.